2010
DOI: 10.1007/s00024-010-0232-8
|View full text |Cite
|
Sign up to set email alerts
|

Runup of Tsunami Waves in U-Shaped Bays

Abstract: The problem of tsunami wave shoaling and runup in U-shaped bays (such as fjords) and underwater canyons is studied in the framework of shallow water theory. The wave shoaling in bays, when the depth varies smoothly along the channel axis, is studied with the use of asymptotic approach. In this case a weak reflection provides significant shoaling effects. The existence of traveling (progressive) waves, propagating in bays, when the water depth changes significantly along the channel axis, is studied. It is show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 40 publications
(48 reference statements)
10
59
0
Order By: Relevance
“…It is possible to find accurate solutions describing nonlinear wave runup on the shores of narrow bays and straits within the framework of shallow water channel theory [9][10][11]. Moreover, it is shown that this theory explains the dynamics of freak waves on the shore and correlates well with their observations [12].…”
Section: Introductionmentioning
confidence: 75%
“…It is possible to find accurate solutions describing nonlinear wave runup on the shores of narrow bays and straits within the framework of shallow water channel theory [9][10][11]. Moreover, it is shown that this theory explains the dynamics of freak waves on the shore and correlates well with their observations [12].…”
Section: Introductionmentioning
confidence: 75%
“…However, even relatively small icebergs have the potential to generate large tsunamis, especially where the seabed bathymetry and coastal topography act to amplify wave height (e.g. [17]). …”
Section: Iceberg-generated Tsunamimentioning
confidence: 99%
“…They found an amplification of the wave amplitude due to the presence of the submarine canyons. In addition, Didenkulova and Pelinovsky (2011) studied the shoaling and run-up in narrow bays and canyons, concluding that when the depth varies smoothly along the channel axis, a weak reflection provides significant shoaling effects.…”
Section: Coastal Engineering 2012mentioning
confidence: 99%